All-Carbon Conductors for Electronic and Electrical Wiring Applications - Cesano, Federico; Uddin, Mohammed Jasim; Lozano, Karen; Zanetti, Marco; Scarano, Domenica (Frontiers in Materials, 2020)
Electrical conductors based on carbons have recently attracted a growing interest due to the prospective of metal replacing. Electrical conductors without metals could represent not only an alternative for traditional wiring, but also a step forward in the progress and advancing of the technology. This result can be achieved by combining high electrical conductivity with other properties, that are dexterity or light weight, environmental stability, high strength and flexibility. For example, the best mechanical properties, high electrical and thermal conductivity of the assembled fibers are all generally associated with low concentration in the fiber backbone and in the individual carbon “building blocks”. In this review, starting from the beginning, the late 19th century, when the carbon filaments glowing in light bulbs stimulated by the Joule heating became the lights for urban streets, we briefly discuss some recent developments in the field of “all-carbon” electrical conductors, that are obtained by assembling nanoscale carbons (i.e. carbon nanotubes, graphene) into macroscopic fibers, yarns and ropes (hereafter fibers). In this perspective, the role played by the chemistry in particular by means of the molecular-level control and doping is emphasized. This contribution provides an appraisal evaluation of the advantages and disadvantages, open questions, most recent results in the field, envisaging the new possible applications.